2008
DOI: 10.1055/s-2007-1011056
|View full text |Cite
|
Sign up to set email alerts
|

1H-MR-Spektroskopie bei Anorexia nervosa: Reversible zerebrale Metabolitenänderungen

Abstract: 1H-MR spectroscopy reveals metabolic changes in the brain of patients with anorexia nervosa, which are reversible under successful therapy. These metabolic changes can be conclusively explained using a biochemical model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We found a higher Cho/Cr ratio in all brain regions of anorexics, except the precuneus, affecting both white and gray matter, which is in agreement with previous studies. 11 , 12 , 13 , 14 This possibly reflects increased cell turnover, and catabolism of lipid membranes with release of fatty acids from phospholipids. In reality, the peak of choline mainly represents glycerophosphocholine.…”
Section: Discussionmentioning
confidence: 99%
“…We found a higher Cho/Cr ratio in all brain regions of anorexics, except the precuneus, affecting both white and gray matter, which is in agreement with previous studies. 11 , 12 , 13 , 14 This possibly reflects increased cell turnover, and catabolism of lipid membranes with release of fatty acids from phospholipids. In reality, the peak of choline mainly represents glycerophosphocholine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous 1.5-T studies, employing 1 H single voxel spectroscopy (SVS), reported increased choline/creatine ratios (Cho/Cr) in the parietooccipital WM of young AN patients. The increase was reversible upon weight increase [43][44][45]. These findings were discussed as transitional alterations of phosphatidylcholine turnover.…”
Section: Introductionmentioning
confidence: 99%